2016
DOI: 10.1016/j.drugalcdep.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescribed use of psychoactive prescription drugs among drug-impaired drivers in Sweden

Abstract: Aims: To determine the prevalence of non-prescribed drug use among subjects suspected of drug-impaired driving with a confirmed intake of a psychoactive prescription drug, and to identify associated factors. Methods:Subjects investigated for drug-impaired driving in Sweden during 2006-2009 with a confirmed intake of diazepam, flunitrazepam, tramadol, zolpidem or zopiclone were identified using the Swedish Forensic Toxicology Database. Information on dispensed prescription drugs was retrieved from the Swedish P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
2
16
0
1
Order By: Relevance
“…In a Swedish study, nonprescribed use was found in 59% of subjects investigated for DUID; the percentage of nonprescribed use was 76% for flunitrazepam, 74% for diazepam, 40% for tramadol, 30% for zopiclone, and 21% for zolpidem. The young and multisubstance users were more likely, whereas subjects with ongoing prescribed treatment with other psychoactive drugs were less likely, to use nonprescribed drugs (Tjäderborn, Jönsson, Sandström, Ahlner, & Hägg, ). In Finland, half of drivers under medicines had a concentration above the therapeutic range and only few cases of sedative‐hypnotic or pregabalin use have been due to appropriate medical use (Kriikku et al, ; Kriikku et al, ).…”
Section: Risks Of Driving Under the Influence Of Drugsmentioning
confidence: 99%
“…In a Swedish study, nonprescribed use was found in 59% of subjects investigated for DUID; the percentage of nonprescribed use was 76% for flunitrazepam, 74% for diazepam, 40% for tramadol, 30% for zopiclone, and 21% for zolpidem. The young and multisubstance users were more likely, whereas subjects with ongoing prescribed treatment with other psychoactive drugs were less likely, to use nonprescribed drugs (Tjäderborn, Jönsson, Sandström, Ahlner, & Hägg, ). In Finland, half of drivers under medicines had a concentration above the therapeutic range and only few cases of sedative‐hypnotic or pregabalin use have been due to appropriate medical use (Kriikku et al, ; Kriikku et al, ).…”
Section: Risks Of Driving Under the Influence Of Drugsmentioning
confidence: 99%
“…Steigende Verschreibungszahlen sind oft mit nichtbestimmungsgemäßem Gebrauch und zunehmender Verfügbarkeit auf dem illegalen Markt assoziiert. Eine epidemiologische Untersuchung auffälliger Kraftfahrer in Schweden ergab, dass 40 % von ihnen Tramadol ohne Verordnung einnahmen [26]. Bei schwer verletzten Fahrern (n =840) in Dänemark unter Einfluss psychoaktiver Substanzen war in 3,2 % aller Fälle Tramadol im Blut der Fahrer nachweisbar, mit Konzentrationen von 2,5 bis 4376 ng/ml.…”
Section: Diskussionunclassified
“…The routines for forensic‐toxicological analyses in Sweden are globally unique: regardless of suspected cause of death or without any expressed request from the medical examiner, the broad range of legal and illegal substances is routinely tested for in each case. The toxicological dataset has previously, at the individual level, been linked to the Swedish National Prescription Registry to identify biochemically the use of prescribed or non‐prescribed psychoactive substances among drug‐impaired drivers and suicide victims . Further, in a recent Swedish study, Hedlund and co‐authors compared prescription history and forensic toxicology with regard to use of psychotropic drugs in homicide offenders and victims (between 2007 and 2009) and vehicle‐related accident controls .…”
Section: Introductionmentioning
confidence: 99%
“…The toxicological dataset has previously, at the individual level, been linked to the Swedish National Prescription Registry to identify biochemically the use of prescribed or non-prescribed psychoactive substances among drug-impaired drivers and suicide victims. [17][18][19][20] Further, in a recent Swedish study, Hedlund and co-authors compared prescription history and forensic toxicology with regard to use of psychotropic drugs in homicide offenders and victims (between 2007 and 2009) and vehicle-related accident controls. 21 Nevertheless, the Swedish forensic dataset has not previously been used, at the individual level, to assess adherence to a broader range of non-psychotropic nonaddictive drugs, or to evaluate the validity of the Swedish National Prescription Registry as a proxy for continuous drug use.…”
Section: Introductionmentioning
confidence: 99%